Neural functions vary by return-to-sport status in participants with anterior cruciate ligament reconstruction: a retrospective cohort study using sub-bands of resting-state functional magnetic resonance - Song, Hongyun; Zhu, Sunan; Pan, Zongyou; Yu, XiaoJing; Xiong, Bing; Dai, Xuesong (Frontiers in Human Neuroscience, 2024)
ObjectiveThis study aimed to characterize the differences in neural function among patients with different functional abilities 2 years after anterior cruciate ligament reconstruction (ACLR).DesignResting-state functional magnetic resonance imaging was performed to obtain blood-oxygen-level-dependent values for ACLR returned to sports coper participants (CP), non-coper participants (NP), and healthy controls (HC). The amplitude of low-frequency fluctuations (ALFF) and regional homogeneity (ReHo) calculated changes in the standard frequency band (SFB) (0.01–0.08 Hz), Slow4 (0.027–0.073 Hz), and Slow5 (0.01–0.027 Hz). Clinical correlations were investigated.ResultsThe right cerebellum_8 and bilateral putamen in SFB, while the right cerebellum_crus2 and left putamen in Slow5 were higher in CP than in NP. The ALLF values of the bilateral putamen in Slow4 were increased, while the right parietal lobule in Slow4 and left upper temporal pole in Slow5 were lower in CP than in HC. The ReHo values in the CP group in the right cerebellum_crus2 was higher than that in the NP group in Slow5 (voxel p < 0.05, cluster p < 0.05, Gaussian Random Field theory correction). Y-balance test was correlated with cerebellum ALFF values; Tegner was moderately correlated with putamen ALFF values (p < 0.05). Knee Injury and Osteoarthritis Outcome Score-sports, International Knee Documentation Committee Subjective Knee Evaluation Form and Tegner scores were correlated with the ReHo values of right cerebellum_crus2 (p < 0.05).ConclusionSubcortical function transfer was performed in patients with ACLR who returned to sports postoperatively: the function of the somatosensory brain area decreased, while that of the subcortical cerebellum and basal ganglia and cerebellum ReHo increased in CP, which was correlated with clinical function. ALFF and ReHo are consistent to some extent, and sub-band studies can reveal information on different brain functions compared to the classical band.